Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To solve for [tex]\(a^2 + b^2\)[/tex] given [tex]\(a = \frac{1}{2 + \sqrt{3}}\)[/tex] and [tex]\(b = \frac{1}{2 - \sqrt{3}}\)[/tex], we follow these steps:
1. Rationalize [tex]\(a\)[/tex] and [tex]\(b\)[/tex]:
- For [tex]\(a\)[/tex]:
[tex]\[ a = \frac{1}{2 + \sqrt{3}} \times \frac{2 - \sqrt{3}}{2 - \sqrt{3}} = \frac{2 - \sqrt{3}}{(2 + \sqrt{3})(2 - \sqrt{3})} \][/tex]
The denominator simplifies as follows:
[tex]\[ (2 + \sqrt{3})(2 - \sqrt{3}) = 4 - 3 = 1 \][/tex]
Therefore,
[tex]\[ a = 2 - \sqrt{3} \][/tex]
- For [tex]\(b\)[/tex]:
[tex]\[ b = \frac{1}{2 - \sqrt{3}} \times \frac{2 + \sqrt{3}}{2 + \sqrt{3}} = \frac{2 + \sqrt{3}}{(2 - \sqrt{3})(2 + \sqrt{3})} \][/tex]
The denominator simplifies as follows:
[tex]\[ (2 - \sqrt{3})(2 + \sqrt{3}) = 4 - 3 = 1 \][/tex]
Therefore,
[tex]\[ b = 2 + \sqrt{3} \][/tex]
2. Calculate [tex]\(a^2\)[/tex] and [tex]\(b^2\)[/tex]:
- For [tex]\(a^2\)[/tex]:
[tex]\[ a^2 = (2 - \sqrt{3})^2 = 4 - 4\sqrt{3} + 3 = 7 - 4\sqrt{3} \][/tex]
- For [tex]\(b^2\)[/tex]:
[tex]\[ b^2 = (2 + \sqrt{3})^2 = 4 + 4\sqrt{3} + 3 = 7 + 4\sqrt{3} \][/tex]
3. Add [tex]\(a^2\)[/tex] and [tex]\(b^2\)[/tex]:
[tex]\[ a^2 + b^2 = (7 - 4\sqrt{3}) + (7 + 4\sqrt{3}) = 7 + 7 = 14 \][/tex]
Thus, the value of [tex]\(a^2 + b^2\)[/tex] is [tex]\(\boxed{14}\)[/tex].
1. Rationalize [tex]\(a\)[/tex] and [tex]\(b\)[/tex]:
- For [tex]\(a\)[/tex]:
[tex]\[ a = \frac{1}{2 + \sqrt{3}} \times \frac{2 - \sqrt{3}}{2 - \sqrt{3}} = \frac{2 - \sqrt{3}}{(2 + \sqrt{3})(2 - \sqrt{3})} \][/tex]
The denominator simplifies as follows:
[tex]\[ (2 + \sqrt{3})(2 - \sqrt{3}) = 4 - 3 = 1 \][/tex]
Therefore,
[tex]\[ a = 2 - \sqrt{3} \][/tex]
- For [tex]\(b\)[/tex]:
[tex]\[ b = \frac{1}{2 - \sqrt{3}} \times \frac{2 + \sqrt{3}}{2 + \sqrt{3}} = \frac{2 + \sqrt{3}}{(2 - \sqrt{3})(2 + \sqrt{3})} \][/tex]
The denominator simplifies as follows:
[tex]\[ (2 - \sqrt{3})(2 + \sqrt{3}) = 4 - 3 = 1 \][/tex]
Therefore,
[tex]\[ b = 2 + \sqrt{3} \][/tex]
2. Calculate [tex]\(a^2\)[/tex] and [tex]\(b^2\)[/tex]:
- For [tex]\(a^2\)[/tex]:
[tex]\[ a^2 = (2 - \sqrt{3})^2 = 4 - 4\sqrt{3} + 3 = 7 - 4\sqrt{3} \][/tex]
- For [tex]\(b^2\)[/tex]:
[tex]\[ b^2 = (2 + \sqrt{3})^2 = 4 + 4\sqrt{3} + 3 = 7 + 4\sqrt{3} \][/tex]
3. Add [tex]\(a^2\)[/tex] and [tex]\(b^2\)[/tex]:
[tex]\[ a^2 + b^2 = (7 - 4\sqrt{3}) + (7 + 4\sqrt{3}) = 7 + 7 = 14 \][/tex]
Thus, the value of [tex]\(a^2 + b^2\)[/tex] is [tex]\(\boxed{14}\)[/tex].
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.